Molecular Markers and Cotton Genetic Improvement: Current Status and Future Prospects. (23rd October 2014) - Malik, Waqas; Ashraf, Javaria; Iqbal, Muhammad Zaffar; Ali Khan, Asif; Qayyum, Abdul; Ali Abid, Muhammad; Noor, Etrat; Qadir Ahmad, Muhammad; Hasan Abbasi, Ghulam
Abstract : Narrow genetic base and complex allotetraploid genome of cotton ( Gossypium hirsutum L.) is stimulating efforts to avail required polymorphism for marker based breeding. The availability of draft genome sequence of G. raimondii and G. arboreum and next generation sequencing (NGS) technologies facilitated the development of high-throughput marker technologies in cotton. The concepts of genetic diversity, QTL mapping, and marker assisted selection (MAS) are evolving into more efficient concepts of linkage disequilibrium, association mapping, and genomic selection, respectively. The objective of the current review is to analyze the pace of evolution in the molecular marker technologies in cotton during the last ten years into the following four areas: (i) comparative analysis of low- and high-throughput marker technologies available in cotton, (ii) genetic diversity in the available wild and improved gene pools of cotton, (iii) identification of the genomic regions within cotton genome underlying economic traits, and (iv) marker based selection methodologies. Moreover, the applications of marker technologies to enhance the breeding efficiency in cotton are also summarized. Aforementioned genomic technologies and the integration of several other omics resources are expected to enhance the cotton productivity and meet the global fiber quantity and quality demands.